HUBUNGAN ANTARA STRES AKADEMIK DENGAN KONTROL EMOSI SANTRI DI PONDOK PESANTREN AL-ITQON JAKARTA BARAT - Hamidah Zahra; Itsna Dzakiah; Ery Yudanti; Ahmad Albianto; Mukhamad Helmiazri; Ahmad Naffakhi (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2026)
Life in an Islamic boarding school (pondok pesantren) requires santri (students) to undergo a demanding academic and religious routine while living far from their families, conditions that may trigger academic stress and demand strong emotional control. This study aims to describe the level of academic stress, describe the level of emotional control, and analyze the relationship between these two variables among santri at Pondok Pesantren Al-Itqon, West Jakarta. A quantitative correlational approach was used, with a population of 100 santri and a sample of 80 respondents determined using the Slovin formula at a 5% margin of error. The instrument was a Likert-scale questionnaire tested for validity and reliability through a try-out with 39 respondents; all items were declared valid, with a Cronbach's Alpha of 0.696. Data were analyzed using normality, linearity, and Pearson correlation tests via SPSS. Results showed that both academic stress and emotional control among santri were at a moderate level. The correlation test revealed a significant negative relationship between academic stress and emotional control (r = -0.263; sig. = 0.018 < 0.05), indicating that higher academic stress corresponds to lower emotional control, and vice versa. Academic stress contributed 6.9% to emotional control, while the remaining 93.1% was influenced by other factors outside this study. These findings are relevant to the concept of mujahadah an-nafs in Islamic psychology, in which self-restraint against pressure is an essential part of santri's moral character.